2019
DOI: 10.33607/bjshs.v2i113.789
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of Changes of Young Swimmers’ Anthropometric Profile in the Time of Intensive Training and Its Correlation with Sports Results

Abstract: Background. Knowledge of the peculiarities of anthropometric indicators, body weight components, and somatotype of athletes is important for coaches, sports scientists, and sports physicians at all stages of perennial training, starting with children’s sport. Often this is seen as an important indicator for identifying talented children in sport. The aim of this study was to determine how the anthropometric and body weight profile of young swimmers (11–12 years) significantly changes during the training period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Geladas et al [ 37 ] also did not find any relationship between anthropometrics and the 100 m race in 13-year-old female swimmers, but they revealed body height, hand length, and horizontal jump association with BA , which explained only 17% of the variance of the 100 m race. Zuozienė and Drevinskaitė [ 41 ] reported in young female swimmers (11.8 ± 0.4) a lack of significant correlation between anthropometrics and the 200 m race. They concluded that, in girls versus boys, anthropometrics predicts swimming performance less.…”
Section: Discussionmentioning
confidence: 99%
“…Geladas et al [ 37 ] also did not find any relationship between anthropometrics and the 100 m race in 13-year-old female swimmers, but they revealed body height, hand length, and horizontal jump association with BA , which explained only 17% of the variance of the 100 m race. Zuozienė and Drevinskaitė [ 41 ] reported in young female swimmers (11.8 ± 0.4) a lack of significant correlation between anthropometrics and the 200 m race. They concluded that, in girls versus boys, anthropometrics predicts swimming performance less.…”
Section: Discussionmentioning
confidence: 99%